Understanding tuberculosis transmission and progression: A prospective cohort study of index cases and close contacts in Moldova. - Rehan R Syed; Donald G Catanzaro; Naomi Hillery; Valeriu Crudu; Elena Tudor; Nelly Ciobanu; Alexandru Codreanu; Maryam Kheirandish Borujeni; Antonino Catanzaro; Timothy C Rodwell (PLoS ONE)
Objectives This study aims to determine the progression rate, risk factors and timeline for the progression from exposure to active tuberculosis (TB) in a high-risk population. Using a prospective cohort in the Republic of Moldova, we investigated pulmonary TB disease progression among close contacts of patients with TB in a low-burden country with high rates of drug-resistant TB. Methods Close contacts of patients with newly diagnosed TB were recruited and monitored to evaluate for progression rates to active TB. Data collected included demographic information, medical and exposure history, and clinical samples. Follow-up clinical evaluations of close contacts were conducted at regular intervals over at least 24 months to monitor for progression to TB disease. Results The overall incidence rate of TB disease among close contacts was 3.7%. Among the close contacts, 2.3% were identified as progressor cases, developing TB disease more than 30 days after index case treatment initiation. Thirteen (1.3%) were co-prevalent cases, diagnosed within 30 days of index case treatment initiation. Identified risk factors for progression included male sex, active tobacco use, prior TB infection, and frequent, prolonged exposure to index cases. Close contacts with daily exposure of more than eight hours had a significantly higher risk of disease progression (adjusted OR: 4.28, 95% CI: 1.79-10.23). Conclusion The incidence of TB disease among close contacts was consistent with global findings, highlighting the need for enhanced diagnostic tools and targeted interventions to manage TB transmission and progression. These results underscore the importance of contact tracing and progression monitoring in low-burden, high drug-resistant TB settings. Future research should focus on developing a better understanding of factors contributing to the risk for and timeline of TB disease progression, and more precise methods, including biomarkers, to identify individuals at the highest risk for progression from TB exposure to active disease.